Styrene resin composition as well as preparation method and application thereof

By adding sheet-structured kaolin and specific coupling agent to styrene-propylene-glycidyl methacrylate tere random copolymer, the high thermal expansion and scaling resistance of the material are solved by combining with the styrene-propylene-glycidyl methacrylate tere random copolymer, the material has a high thermal expansion, cold expansion and scratch resistance. The problem of insufficient damage performance has achieved the preparation of low CLTE and scratch-resistant styrene resin compositions, which are suitable for automotive and electronic parts.

CN119286181AActive Publication Date: 2025-01-10WUHAN JINFA TECH CO LTD +1

Patent Information

Application Number
CN202411493923.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-10
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The expansion rate of existing styrene resin materials is high during thermal expansion and contraction, resulting in larger gaps between parts, affecting driving safety and comfort, and insufficient scratch resistance, making it difficult to meet the needs of automobiles, electronics and electrical fields. .

Method used

A styrene resin composition is adopted, including styrene resin, sheet-structured kaolin, a compound dispersant of silane coupling agent and titanate coupling agent, and styrene-propylene-glycidyl methacrylate trimer Random copolymers are used as compatibilizers to form high dispersion and high stability materials through the twin screw extrusion mechanism.

Benefits of technology

It realizes low linear thermal expansion dilution, reduces the impact of material size on temperature changes, improves scratch resistance and dimensional stability, and is suitable for parts manufacturing of automobiles and electronic appliances.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a styrene resin composition which comprises the following components in parts by weight: 70 parts of styrene resin; 5-15 parts of kaolin with a lamellar structure; 0.5 to 1.5 parts of a dispersing agent; 2-5 parts of a compatilizer; wherein the dispersing agent is a compound of a silane coupling agent and a titanate coupling agent, and the weight ratio of the silane coupling agent to the titanate coupling agent is (1.5-3): 1; the compatilizer is selected from a styrene-acrylonitrile-glycidyl methacrylate ternary random copolymer. According to the invention, the kaolin with a specific specific surface area and a lamellar structure, the dispersing agent with a specific ratio and the styrene-acrylonitrile-glycidyl methacrylate ternary random copolymer with a specific GMA content are selected, so that the scratch resistance and the dimensional stability can be improved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a preparation method and application of a styrene resin composition. Background Art

[0002] ABS (acrylonitrile-butadiene-styrene) is a terpolymer of acrylonitrile-butadiene-styrene. Since ABS resin coordinates the superior properties of the three components, it has excellent impact strength, good processing performance and chemical stability, is easy to mold, and the products are glossy, tough and flexible, with excellent comprehensive performance. ABS resin is widely used in the automotive industry, electronic and electrical industry, light industrial appliances, textiles and construction industries with its excellent comprehensive performance. In recent years, the automotive industry has paid more and more attention to the assembly gap and part scratches in the car. The assembly gap of parts in the car mainly comes from the thermal expansion and contraction of the joint parts in the car. The larger assembly gap will directly affect the driver and passengers' feelings, and even affect the driving safety. The scratches on the parts in the car not only affect the driving experience, but also affect people's mood if they accumulate too much.

[0003] Not only in the automotive field, but also in other fields such as home appliances, electronic appliances, etc., products with both low CLTE and scratch resistance will undoubtedly bring consumers a healthier and more comfortable experience. Styrene alloy materials are widely used in many national fields, so the development and design of materials with both low CLTE and scratch resistance has important value and significance. Summary of the invention

[0004] The object of the present invention is to provide a scratch-resistant, low-CLTE styrene resin composition, and a preparation method and application thereof.

[0005] The present invention is achieved through the following technical solutions: A styrene resin composition, comprising the following components in parts by weight: 70 parts of styrene resin; 5-15 parts of lamellar kaolin; Dispersant 0.5-1.5 parts; 2-5 parts of compatibilizer; Wherein, the dispersant is a compound of a silane coupling agent and a titanate coupling agent, and the weight ratio of the silane coupling agent to the titanate coupling agent is (1.5-3):1; The compatibilizer is selected from styrene-acrylonitrile-glycidyl methacrylate ternary random copolymer, the weight content of glycidyl methacrylate is in the range of 2.0-3.3wt%, and the weight content of styrene units is in the range of 65-75wt%; The specific surface area of ​​the lamellar kaolin is 4-22m 2 / g, and the kaolin surface is coated with a dispersant.

[0006] Preferably, the weight ratio of the silane coupling agent to the titanate coupling agent is (1.9-2.6):1.

[0007] Preferably, the weight content of glycidyl methacrylate in the styrene-acrylonitrile-glycidyl methacrylate terpolymer is in the range of 2.6-2.9 wt %, and the weight content of the styrene unit is in the range of 68-72 wt %.

[0008] Among them, the test method of GMA content is: weigh a certain amount of epoxy resin sample, add it to hydrochloric acid acetone solution to dissolve. After adding the indicator, titrate with ml-sodium hydroxide standard solution and record the consumed volume. Calculate the epoxy value by the formula: Epoxy value = (V0 - V1) × N / W, where V0 is the volume of NaOH consumed in blank titration, V1 is the volume of NaOH consumed in sample titration, N is the concentration of NaOH solution, and W is the sample weight.

[0009] The styrene / acrylonitrile / glycidyl methacrylate ternary random copolymer can be a commercially available product or can be prepared in-house. The preparation method is as follows: styrene, acrylonitrile and glycidyl methacrylate are subjected to free radical polymerization by suspension polymerization according to the proportion of each unit. The reaction temperature is 60-140° C. and the pressure in the reactor is 0.1-1.2 MPa. The styrene / acrylonitrile / glycidyl methacrylate ternary random copolymer is obtained.

[0010] Preferably, the specific surface area of ​​the lamellar kaolin is 6-16m 2 / g. The test method of specific surface area is: put the powder sample to be tested in a U-shaped sample tube, let the mixed gas containing a certain proportion of adsorbent flow through the sample, determine the adsorption amount of the adsorbent molecule (N2) of the sample to be tested according to the change of gas concentration before and after adsorption, and calculate the specific surface area of ​​the powder to be tested.

[0011] The styrene resin is selected from at least one of ABS, ASA and AES. Preferably, in the styrene resin composition of the present invention, the weight percentage of the styrene resin is not less than 65wt%. At the same time, preferably, the melt index of the styrene resin is in the range of 15-25g / 10min (220kg, 10°C).

[0012] The silane coupling agent is selected from at least one of an ethoxysilane coupling agent, an aminosilane coupling agent, and a methacrylate silane coupling agent; wherein the aminosilane coupling agent may be N-(2-aminoethyl)-3-aminopropyltrimethoxysilane; optionally, the brand of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane may be: KH792 of Xiangfeng Weiye.

[0013] The titanate coupling agent may be diisopropyl bis(triethanolamine)titanate; optionally, the brand of diisopropyl bis(triethanolamine)titanate may be: HY-1803 of Jessica Chemical.

[0014] It is possible to choose whether to add 0-2 parts of auxiliary agent according to actual conditions, and the auxiliary agent is selected from at least one of an antioxidant, a lubricant, and a light stabilizer.

[0015] The preparation method of the styrene resin composition comprises the following steps: premixing the dispersant with the lamellar kaolin according to the proportion, then uniformly mixing with other components, and extruding and granulating through a twin-screw extruder to obtain the styrene resin composition. The temperature range of the screw barrel is 220-250°C.

[0016] The styrene resin composition is used to prepare electrical appliance housings and vehicle-mounted parts.

[0017] The present invention has the following beneficial effects: The present invention selects a styrene-acrylonitrile-glycidyl methacrylate ternary random copolymer with a specific GMA content as a compatibilizer and a specific dispersant, which can improve the dispersion effect of flaky kaolin. The higher the specific surface area of ​​kaolin, the stronger the ability of combining with the compatibilizer and the dispersant. However, the higher the specific surface area of ​​kaolin, the more difficult it is to disperse. Therefore, when the specific surface area of ​​kaolin is within a specific range, a part of kaolin forms a dispersed state of a flaky structure on the surface to achieve a scratch-resistant effect, and the other part of kaolin is better dispersed in a resin matrix, which reduces the linear thermal expansion dilution of the system, so that the influence of the unit length of the material on the size with temperature changes is reduced, thereby improving the dimensional stability. DETAILED DESCRIPTION

[0018] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0019] The sources of raw materials used in the present invention are as follows: ABS resin: Shanghai Gaoqiao Petrochemical Company, brand ABS 8434; AES resin: Japan TECHNO, AES 491; The lamellar kaolin was purchased from the CMP series of Wanzhu Mining. Raw materials with different specific surface areas were obtained through screening and testing: Lamellar kaolin A: Specific surface area is 4m 2 / g,; Lamellar kaolin B: Specific surface area is 8m 2 / g,; Lamellar kaolin C: Specific surface area is 16m 2 / g, Wanzhu Mining; Lamellar kaolin D: Specific surface area is 20m 2 / g,; Lamellar kaolin E: Specific surface area is 2m 2 / g,; Lamellar kaolin F: Specific surface area is 30m 2 / g,; Silane coupling agent: N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, Xiangfeng Weiye, KH792; Titanate coupling agent: diisopropyl bis(triethanolamine)titanate, Jessica Chemical, HY-1803; Antioxidant: a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, produced and provided by Ciba; Lubricant: Pentaerythritol stearate, LOZA company, brand name GLYCOLUBE-P.

[0020] Compatibilizer A: styrene-acrylonitrile-glycidyl methacrylate terpolymer, GMA content is 2.0wt%, weight content of styrene unit is 74wt%, homemade; Compatibilizer B: styrene-acrylonitrile-glycidyl methacrylate terpolymer, GMA content is 2.6wt%, weight content of styrene unit is 71wt%, homemade; Compatibilizer C: styrene-acrylonitrile-glycidyl methacrylate terpolymer, GMA content is 2.9wt%, weight content of styrene unit is 69wt%, homemade; Compatibilizer D: styrene-acrylonitrile-glycidyl methacrylate terpolymer, GMA content is 3.3wt%, weight content of styrene unit is 66wt%, homemade; Compatibilizer E: styrene-acrylonitrile-glycidyl methacrylate terpolymer, GMA content is 1.3wt%, weight content of styrene unit is 70wt%, homemade; Compatibilizer F: styrene-acrylonitrile-glycidyl methacrylate terpolymer, GMA content is 4.0wt%, weight content of styrene unit is 70wt%, homemade; The homemade method is: according to the proportion of each unit, styrene, acrylonitrile and glycidyl methacrylate are subjected to free radical polymerization by suspension polymerization method, the reaction temperature is 60-140°C, and the pressure in the reactor is 0.1-1.2MPa; a styrene / acrylonitrile / glycidyl methacrylate ternary random copolymer is obtained.

[0021] Embodiment and comparative example Preparation method of styrene resin composition: After mixing all components evenly, add them into the main barrel of a twin-screw extruder (screw diameter is 35 mm, aspect ratio L / D=48). The temperature of each section of the main barrel (from the feed port to the die outlet) is controlled at 220°C, 235°C, 245°C, 250°C, and 245°C respectively, the twin screw speed is 300 rpm, and the extruded material strips are cooled in a water tank and pelletized to obtain a styrene resin composition.

[0022] Various test methods: (1) Scratch resistance: The test was conducted in accordance with Geely Q / JLY J7110536B-2016 standard. The scraper speed of the electric scratch tester was set to (1000±50) mm / min, the pressure was 10N, and the head was 1mm. The scratch tester scraper was used to make parallel scratches of 40 mm in length every 2 mm in one direction on the surface of the plastic sample. At least 20 parallel lines were drawn. The sample was then rotated 90° and the above operation was repeated to form a grid. At least three parallel samples were scratched and the color difference △L before and after the scratch area test was measured.

[0023] (2) CLTE test, tested in accordance with ISO 11359-2:2011 standard.

[0024] Table 1: Content of each component of styrene resin in Examples 1-5 (parts by weight) and test results Example 1 Example 2 Example 3 Example 4 Example 5 ABS resin 70 70 70 70 AES Resin 70 Lamellar Kaolin A 10 15 10 10 10 Silane coupling agent 0.6 0.9 0.66 0.72 0.75 Titanate coupling agent 0.4 0.6 0.34 0.28 0.25 Compatibilizer A 3 5 3 3 3 Antioxidants 0.2 Lubricants 0.2 △L 0.8 0.6 0.7 0.7 0.8 CLTE / (μm / (m*℃)) 62 64 58 59 62 It can be seen from Examples 1 / 3 / 4 / 5 that the preferred compounding ratio of silane coupling agent / titanate coupling agent has better scratch resistance and lower CLTE.

[0025] Table 2: Content of each component of styrene resin in Examples 6-11 (parts by weight) and test results Example 6 Example 7 Example 8 Example 9 Example 10 Embodiment 11 ABS resin 70 70 70 70 70 70 Lamellar Kaolin A 10 10 10 Lamellar Kaolin B 10 Lamellar Kaolin C 10 Lamellar Kaolin D 10 Silane coupling agent 0.6 0.6 0.6 0.6 0.6 0.6 Titanate coupling agent 0.4 0.4 0.4 0.4 0.4 0.4 Compatibilizer A 3 3 3 Compatibilizer B 3 Compatibilizer C 3 Compatibilizer D 3 △L 0.7 0.7 0.8 0.6 0.5 0.8 CLTE / (μm / (m*℃)) 56 59 63 54 52 62 It can be seen from Examples 1 / 6 / 7 / 8 that the preferred lamellar kaolin has better scratch resistance and dimensional stability than the surface area.

[0026] It can be seen from Examples 1 / 8 / 10 / 11 that when the compatibilizer with a GMA / st unit content is preferred, the scratch resistance and dimensional stability are better.

[0027] It can be seen from the above examples that the ΔL of the styrene-based resin of the present invention is below 0.9 and the CLTE is below μ65 m / (m*°C).

[0028] Table 3: Content of each component (parts by weight) and test results of styrene resin in comparative examples 1-6 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 ABS resin 70 70 70 70 70 70 Lamellar Kaolin A 10 10 10 10 Lamellar Kaolin E 10 Lamellar Kaolin F 10 Silane coupling agent 0.5 0.8 0.6 0.6 0.6 0.6 Titanate coupling agent 0.5 0.2 0.4 0.4 0.4 0.4 Compatibilizer A 3 3 1 3 3 Compatibilizer D 7 △L 1.4 1.3 1.8 1.5 1.1 1.2 CLTE / (μm / (m*℃)) 67 68 72 74 68 69 Table 4: Comparative Examples 7-8 Styrene Resin Component Content (Parts by Weight) and Test Results Comparative Example 7 Comparative Example 8 ABS resin 70 70 Lamellar Kaolin A 10 10 Silane coupling agent 0.6 0.6 Titanate coupling agent 0.4 0.4 Compatibilizer E 3 Compatibilizer F 3 △L 1.2 1.3 CLTE / (μm / (m*℃)) 71 72 It can be seen from Comparative Example 1 / 2 that when the ratio of the silane coupling agent to the titanate coupling agent is not within the scope of the present invention, the scratch resistance and dimensional stability are poor.

[0029] It can be seen from Comparative Examples 3 / 4 that when the content of the styrene-acrylonitrile-glycidyl methacrylate terpolymer is too high or too low, the scratch resistance and dimensional stability are poor.

[0030] It can be seen from Comparative Examples 5 / 6 that if the specific surface area of ​​the lamellar kaolin is too high or too low, the scratch resistance and dimensional stability are poor.

[0031] It can be seen from Comparative Examples 7 / 8 that when the GMA content in the compatibilizer is not within the range of the present invention, the scratch resistance and dimensional stability are poor.

Claims

1. A styrene resin composition, characterized in that: By weight, it includes the following components: 70 parts of styrene resin; 5-15 parts of lamellar kaolin; Dispersant 0.5-1.5 parts; 2-5 parts of compatibilizer; Wherein, the dispersant is a compound of a silane coupling agent and a titanate coupling agent, and the weight ratio of the silane coupling agent to the titanate coupling agent is (1.5-3):1; The compatibilizer is selected from a styrene-acrylonitrile-glycidyl methacrylate terpolymer, wherein the weight content of the glycidyl methacrylate unit is in the range of 2.0-3.3wt%, and the weight content of the styrene unit is in the range of 65-75wt%; The specific surface area of ​​the lamellar kaolin is 4-22m 2 / g, and the kaolin surface is coated with a dispersant.

2. The styrene resin composition according to claim 1, characterized in that The weight ratio of the silane coupling agent to the titanate coupling agent is (1.9-2.6):

1.

3. The styrene resin composition according to claim 1, characterized in that: The weight content of glycidyl methacrylate in the styrene-acrylonitrile-glycidyl methacrylate terpolymer is in the range of 2.6-2.9wt%, and the weight content of the styrene unit is in the range of 68-72wt%.

4. The styrene resin composition according to claim 1, characterized in that The specific surface area of ​​the lamellar kaolin is 6-16m 2 / g.

5. The styrene resin composition according to claim 1, characterized in that: The styrene resin is selected from at least one of ABS, ASA and AES.

6. The styrene resin composition according to claim 1, characterized in that: The silane coupling agent is selected from at least one of ethoxysilane coupling agent, aminosilane coupling agent and methacrylate silane coupling agent; the titanate coupling agent is selected from diisopropyl bis(triethanolamine) titanate.

7. The styrene resin composition according to claim 1, characterized in that: By weight, the invention further comprises 0-2 parts of auxiliary agents, wherein the auxiliary agents are selected from at least one of antioxidants, lubricants and light stabilizers.

8. The method for preparing the styrene resin composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: According to the ratio, the dispersant is premixed with the lamellar kaolin, and then mixed with other components uniformly, and extruded and granulated by a twin-screw extruder to obtain a styrene resin composition.

9. Use of the styrene resin composition according to any one of claims 1 to 7, characterized in that: Used for preparing electrical housings and vehicle-mounted parts.

Citation Information

Patent Citations

  • High-temperature-resistant electroplating-grade ABS resin and preparation method thereof

    CN111875897A

  • Polycarbonate alloy material as well as preparation method and application thereof

    CN117624860A

  • Low-gloss heat-resistant ABS resin composition and preparation method therefor

    WO2016106836A1

Cited By

  • Styrene resin composite material as well as preparation method and application thereof

    CN120137341A